Investigation on the performance and efficiency droop behaviors of InGaN/GaN multiple quantum well green LEDs with various GaN cap layer thicknesses. (July 2016) - Yang, J.; Zhao, D.G.; Jiang, D.S.; Chen, P.; Zhu, J.J.; Liu, Z.S.; Le, L.C.; He, X.G.; Li, X.J.; Liu, J.P.; Zhang, L.Q.; Yang, H.
Abstract: The performance and efficiency droop behaviors of InGaN/GaN multiple quantum well (MQW) green LEDs with various low temperature grown GaN cap (LT-cap) layer are investigated. It is found that the output power increases when a thin LT-cap layer (0.37 nm) is inserted and it decreases as the LT-cap layer thickness increases up to 1.5 nm. In addition, the apparent efficiency droop decreases when the thickness of LT-cap layer increases from 0 to 1.5 nm. However, the related physical mechanisms are different. When the relatively thin LT-cap layers are inserted, the carrier confinement effect of QWs enhances due to the increased In content of InGaN QWs. In this case, electrons are hardly to escape from MQW region to p-GaN region, which results in a relatively high output power at high injection current, thus a small efficiency droop is obtained. However, when the LT-cap layer thickness is relatively thick, due to the large defect density of InGaN/GaN MQWs, although the small efficiency droop also can be observed, the relatively low output power is obtained at all injection currents. Highlights: Inserting a thin LT-cap layer is benefit for fabricating green LEDs due to a high output power at high injection current. The apparent efficiency droop always decreases when the thickness of LT-cap layer increases. Due to the inferior interface quality and large defect density in samples with thicker LT-cap layer, a lower output power is obtained.